Implementação de inovações curriculares no Ensino Médio e formação continuada de professores: as lições de uma experiência - Cerqueira, Dermeval Santos (2003)
The subject of this present work The implementation of curriculum innovation in high school teaching and teacher continuing graduation: lessons of experience aims to search for directions for high school teachers undergraduation hoping themto get used of new curriculum elements such as problem solution, the interdisciplinary connection, contextualization concernig the Mathematics curriculumfor higt school teaching. It has got as the main problem the strength of teachers continuing undergraduation projects which are supported by thematization of practice for the implementation of curriculum innovation. Therefore, the main purpose is to contribute to the improvement of the continuing undergraduation process of working teachers, engaging them to the curriculum innovation process. By recording the different moments of such formation project and analyzing some results of this work, we could identify the facts which contribute positively so that purposes can be reached and the difficulties faced on